The impact of probiotics on testosterone synthesis in the TM3 cell line - Yu Ha Shim; JuYi Jang; Ilseon Jung; Yu Jin Kim; Yun Dong Koo; Tae Ho Lee; Jae Ho Lee; Dae Keun Kim (Clinical and Experimental Reproductive Medicine, 2026)
Objective: This study aimed to investigate the effects of specific probiotic strains on the endocrine activity of Leydig cells, which are essential for testosterone production. We focused on the potential influence of probiotics on testosterone synthesis and mitochondrial functionality within these cells.Methods: The TM3 Leydig cell line was utilized to assess the effects of three probiotic strains: Lacticaseibacillus rhamnosus, Limosilactobacillus fermentum, and Bifidobacterium longum subsp. longum. The analyses evaluated key aspects of Leydig cell function, including endocrine signaling pathways, cellular proliferation, gene and protein expression related to testosterone biosynthesis, and mitochondrial function.Results: The probiotic strains significantly enhanced the expression of key proteins involved in testosterone synthesis and upregulated mitochondrial activity compared to control cells. Notably, these effects were observed across all three probiotic strains, suggesting a positive impact on both testosterone production and mitochondrial function.Conclusion: The findings suggest that probiotic supplementation can modulate testosterone synthesis and improve mitochondrial functionality in Leydig cells. These results underscore the potential of probiotics as modulators of male reproductive health, with possible therapeutic applications in conditions such as male hypogonadism.